Implementing post-discharge 48-hour scripted call for patients with heart failure: An evidence-based practice quality improvement project - Ruggiri, J.C.; Milner, K.A.; Buonocore, D. (MEDSURG Nursing, 2019)
Post-discharge call programs are a simple and effective way to identify and intervene for patient care issues that may occur after discharge. Nurses play a key role in these programs and can lead quality improvement projects on their units to improve patient care during the transition from hospital to home. © 2019, Anthony J. Jannetti Publications, Inc.. All rights reserved.
Keywords: dept.nur; peer-reviewed; ⛔ No DOI found

Cultural considerations in the care of psychiatric patients: a case study on fright - Green, Cheryl (Journal of National Black Nurses Association, 2019)
Place: Silver Spring, Maryland
Keywords: Cultural Competence; Cultural Sensitivity; Fear; Female; Health Care Delivery; Medicine; Herbal; Multidisciplinary Care Team; Patient Centered Care; Psychiatric Patients; Young Adult; dept.nur; peer-reviewed; ⛔ No DOI found

Calm in Chaos: Prose on Tensions of Hate and Distrust in Society - Green, Cheryl; Green, Joshua William (Westbow Press, 2019)
Keywords: Hate; Poetry; Poetry; Racism; dept.nur; faculty_collection

Scope and standards of practice - Resha, Cheryl Ann (School Nursing: A Comprehensive Text, 2019)
Produced in cooperation with the National Association of School Nurses, this text includes comprehensive coverage of the multiple facets of school nursing—from the foundations of practice and the roles and functions of a school nurse through episodic and chronic illness and behavioral issues, to legal issues and leading and managing within school settings. Written and edited by school nurses and pediatric experts, it features real-world-tested, best practices based on evidence and experience. There’s content here that you won’t find in other books, such as health assessments, individualized health plan development, mental health conditions including adolescent depression, contemporary legal issues, and current policy statements essential to school nursing.
Google-Books-ID: VXWmDwAAQBAJ
Keywords: Medical / Nursing / General; dept.nur

Fibromyalgia treatment and management considerations for nurse practitioners - Stournaras, Dana; Petrovic, Kimberly (Journal of the American Association of Nurse Practitioners, 2019)
The purpose of this case study is to examine the role of the nurse practitioner in the management and treatment of a 35-year-old female patient diagnosed with several conditions, including fibromyalgia posttraumatic stress disorder, anxiety, and depression. Fibromyalgia is a chronic, nonprogressive rheumatic condition with cardinal symptoms of widespread pain and fatigue; it affects more than 5 million people in the United States. This case study examines the nurse practitioner's role in managing fibromyalgia. Benzodiazepines and opioids may be prescribed for treatment of symptoms but prove ineffective, thus contributing to dependency issues. Controversy exists over classification of fibromyalgia as a rheumatologic condition versus a mental health disorder. Fibromyalgia frequently is accompanied by anxiety and depression, making this illness difficult to diagnose and treat.
2 citations (Crossref) [2023-10-31] tex.eissn: 2327-6924 tex.unique-id: ISI:000480702800008
Keywords: Adult; Anxiety; Depression; Female; Fibromyalgia; Humans; Nurse Practitioners; Practice Patterns; Nurses'; Stress Disorders; Post-Traumatic; Treatment Outcome; adult; advanced practice nursing; anxiety; benzodiazepines; chronic disease; depression; dept.nur; female; fibromyalgia; hearing loss; human; nurse practitioner; nurse practitioners; nursing practice; opioids; pain; pathophysiology; peer-reviewed; posttraumatic stress disorder; psychology; role; role concept; treatment outcome

International board certified lactation consultants’ practices regarding supplemental feeding methods for breastfed infants - Penny, Frances; Judge, Michelle P.; Brownell, Elizabeth A.; McGrath, Jacqueline M. (Journal of Human Lactation, 2019)
Background: According to the Baby Friendly Hospital Initiative, when supplementary feeding occurs, mothers should be counseled on the use and risks of feeding bottles and teats. To help support this initiative it is important to understand the supplementation practices of Internationally Board Certified Lactation Consultants (IBCLC)®. Research aims: To determine (1) if the location of an IBCLC’s practice has any impact on supplemental feeding methods; (2) the preferred methods of and the main reasons for supplementation; (3) the level of an IBCLC’s confidence with supplemental feeding methods; (4) who is making supplemental feeding decisions; and (5) if there are geographical differences among supplementation choices and reasons for supplementation. Methods: An exploratory, descriptive, cross sectional survey of IBCLCs was conducted to generate data about their use of supplemental feeding methods. The survey was sent via email invitation through the International Board of Lactation Consultant’s Board of Examiners, with a response rate of 11.5% (N = 2,308). Results: There was no standard method of supplementation among participants. Participants indicated that they were confident advising mothers on alternative feeding methods. Only 17.6% (n = 406) of participants reported that the IBCLC was the caregiver who recommended the method of supplementation used. The majority of participants believed the Supplemental Feeding Tube Device SFTD) best preserves the breastfeeding relationship, and this was their preferred method of supplementation. However, the bottle was ranked as the number one method used in the United States, Australia, and Canada. The use of alternative feeding methods may be overwhelming to the mother. Conclusion: Supplementation by alternative feeding methods might help preserve the breastfeeding relationship and help reach the World Health Organization’s goal of increasing exclusive breastfeeding rates. © The Author(s) 2019.
4 citations (Crossref) [2023-10-31] Citation Key Alias: pop00187 tex.type: [object Object]
Keywords: *Breast Feeding/sn [Statistics & Numerical Data]; *Consultants; *Infant Formula/sn [Statistics & Numerical Data]; *Practice Patterns; Nurses'; Adult; Breast Feeding; Certification; Consultants; Cross-Sectional Studies; Female; Global Health; Humans; Infant Formula; Infant; Newborn; International Board Certified Lactation Consultant; Middle Aged; Postnatal Care; Practice Patterns; Nurses'; Pregnancy; Surveys and Questionnaires; Young Adult; adult; artificial feeding; artificial milk; breast feeding; breastfeeding support; certification; consultation; cross-sectional study; dept.nur; female; global health; human; middle aged; newborn; nursing practice; peer-reviewed; postnatal care; pregnancy; questionnaire; supplementation; young adult

Effect of using the conversation project as a teaching tool to increase graduate student nurses' self confidence in discussing end-of-life wishes with patients and families - O'Sullivan, Cynthia; O'Shea, Eileen (Nursing Research, 2019)
tex.eissn: 1538-9847 tex.unique-id: ISI:000461444300077
Keywords: dept.nur; peer-reviewed; ⛔ No DOI found

Workplace incivility: Nurse leaders as change agents - Green, Cheryl Ann (Nursing Management, 2019)
An abstract is unavailable.
7 citations (Crossref) [2023-10-31]
Keywords: Humans; Interprofessional Relations; Leadership; Nursing Staff; Organizational Innovation; Workplace; dept.nur; human; leadership; nursing staff; organization; peer-reviewed; public relations; workplace

Bereavement care to minimize bereaved parents' suffering in their lifelong journey towards healing - Denhup, Christine (Applied Nursing Research, 2019)
This article presents select findings from an interpretive phenomenological study which aimed to describe the lived experience of parental bereavement. Six parents, each of whom experienced the death of a child due to cancer at least one year prior, participated in conversational interviews to share what it has been like for them since their child's death. Heideggerian (1962) phenomenology provided the philosophical underpinnings of the study, while van Manen's (1997) phenomenological method guided data collection and analysis. From this methodological approach, a structure of the meaning of parental bereavement experience was revealed. Profound suffering emerged as one essential theme. Pertinent findings related to this theme are discussed. Parents share ways others might minimize their suffering and provide support in their lifelong journey towards healing. Findings will enhance nurses' practice of providing bereavement care, which is an expectation of quality palliative care. Copyright © 2019 Elsevier Inc. All rights reserved.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/134-579-857-152-025 tex.type: [object Object]
Keywords: *Adaptation; Psychological; *Bereavement; *Neoplasms/mo [Mortality]; *Nurse's Role/px [Psychology]; *Nursing Staff; Hospital/px [Psychology]; *Parents/px [Psychology]; *Stress; Psychological/px [Psychology]; Adaptation; Psychological; Adult; Attitude to Death; Bereavement; Child death; Female; Humans; Male; Middle Aged; Neoplasms; Nurse's Role; Nursing Staff; Hospital; Palliative care; Parental bereavement; Parents; Stress; Psychological; Suffering; adult; attitude to death; bereavement; child parent relation; coping behavior; dept.nur; female; human; male; mental stress; middle aged; mortality; neoplasm; nurse attitude; nursing staff; peer-reviewed; psychology

Identification of patients' spiritual needs using a spiritual health assessment tool - Green, Cheryl Ann (Creating Healthy Work Environments, 2019)
Citation Key Alias: lens.org/090-145-772-380-333 tex.type: [object Object]
Keywords: dept.nur; ⛔ No DOI found

Orientation Learning Needs of Adjunct Clinical Faculty in the United States - Sousa, Monica P.; Resha, Cheryl A. (Nursing Education Perspectives, 2019)
Aim: The aim of the study was to examine the orientation learning needs of adjunct clinical faculty as they transition from expert clinicians to novice educators. Background: Schools of nursing are increasingly using adjunct clinical faculty because of the nurse faculty shortage. Retention is a concern. Method: This descriptive quantitative study used the Needs Assessment Survey for Topic Inclusion in a Guide to Orientation. Adjunct clinical faculty rated the level of importance of orientation topics and if they received needed information. Results: The majority of topics were found to be rated very important or important. Several items deemed very important or important were either not discussed or not sufficiently discussed in orientation. Conclusion: The information obtained demonstrates the vast amount of information that adjunct clinical faculty want and need in an orientation. © 2019 Lippincott Williams & Wilkins.
2 citations (Crossref) [2023-10-31]
Keywords: Adjunct Clinical Faculty; Clinical Nurse Faculty; Clinical Teaching; Faculty Orientation; Faculty; Nursing; Humans; Needs Assessment; Nurses; Transition Into Academia; United States; article; clinical education; clinician; dept.nur; human; learning; needs assessment; nurse; nursing education; peer-reviewed; quantitative analysis